"Someone has to be the First": Tracing Uruguay's Marijuana Legalisation Through Counterfactuals. Issue 2 (August 2020) - von Hoffmann, Jonas
Why did Uruguay become the first country in the world to legalise marijuana in 2013? Based on extensive original research and unprecedented review of secondary sources, the article assesses alternative explanatory accounts through a unique combination of process tracing and counterfactual analysis. By tracing cannabis reform in Uruguay both as it was and was not but could have been in the absence of hypothesised explanatory factors, the article assesses the role of these factors in the causal story. Specifically, the article shows how and why political will and social mobilisation influenced both the reform process and outcome. In doing so, the article cuts through the haze of rival explanations to present the clearest picture of drug policy reform in Uruguay to date.